Experiencias y narraciones en torno al uso de tecnologías anticonceptivas (1970-2010): Una propuesta para su análisis y discusión - Ramírez Hernández, Marcela (2015)
From the 1960’s on, a wide range of new contraceptive technologies began to enter the country, most of them targeted to be used by women. Fifty-five years later, what can we establish about her experiences? This paper inquires, based on the narratives from a group of nine San Jose women aged between 25 and 71, and their impressions and experiences on the use of contraception. Its use can cause side effects in users, plus biological processes produced by the intervention of chemicals in the body. It makes statetemens on power-related issues, resistance, negotiations and gender constructions in couple relationships. Their study is approached from the interpretative contributions allowed by the concepts of habitus, gender performativity and disciplinary mechanisms, to recognize the transformation and/or continuity of power relationships that develop around this particular issue, also linked with the experience of female sexuality and childbearing decisions.